Civil and Political Rights in Constitutionality of Accommodation of Individual Candidates and Elimination of Presidential Thresholds from the Perspective of the 1945 Constitution - Sabirin, Ahmad; Notoprayitno, Maya Indrasti; Ramadhan, Jihad; Herfian, Raafid Haidar (International Journal of Law and Public Policy (IJLAPP), 2023)
Indonesia will hold presidential and vice-presidential elections, however, currently, the election mechanism for presidential and vice-presidential candidates only accommodated nominations through political parties and also still uses the provisions of the Presidential Threshold. Indonesia is a country that adheres to a democratic system which of course strongly adheres to the principle of people's sovereignty which guarantees the rights of all its citizens, and should also accommodate the mechanism of presidential nomination through individual or independent channels. Thus, blocking the rights of some citizens who wish to nominate themselves through non-political party channels, indicates that democratic principles have not been implemented properly. Based on this background, the formulation of the problem, how is the accommodation of individual candidates in the presidential election and the elimination of the presidential nomination threshold in Indonesia and the solution as a democratic country from the perspective of the 1945 Constitution? The type of research used is juridical-normative research, in designing the format of the mechanism for the recruitment of candidates for president and vice president in the electoral system in Indonesia, it must be by democratic principles, this is based on the preamble of the 1945 Constitution as the highest law in Indonesia that adheres to the principle of people's sovereignty. To implement democratic principles well in general elections, Indonesia needs to apply a two-door recruitment mechanism format, which is a format that provides two kinds of doors as a nomination pathway. Based on this, it is necessary to immediately implement and realize a two-door nomination mechanism, namely through political parties and also through individual or independent channels in the Presidential Election and it is also necessary to remove the Presidential Threshold to carry out democratic elections. and justice to maintain peace and prosperity.